Financial Deepening, Terms of Trade Shocks, and Growth Volatility in Low-Income Countries - Kpodar, Kangni (IMF Working Papers; Working Paper, 2019)
This paper contributes to the literature by looking at the possible relevance of the structure of the financial system-whether financial intermediation is performed through banks or markets-for macroeconomic volatility, against the backdrop of increased policy attention on strengthening growth resilience. With low-income countries (LICs) being the most vulnerable to large and frequent terms of trade shocks, the paper focuses on a sample of 38 LICs over the period 1978-2012 and finds that banking sector development acts as a shock-absorber in poor countries, dampening the transmission of terms of trade shocks to growth volatility. Expanding the sample to 121 developing countries confirms this result, although this role of shock-absorber fades away as economies grow richer. Stock market development, by contrast, appears neither to be a shock-absorber nor a shock-amplifier for most economies. These findings are consistent across a range of econometric estimators, including fixed effect, system GMM and local projection estimates.